2014
DOI: 10.1111/jcmm.12341
|View full text |Cite
|
Sign up to set email alerts
|

Th17 can regulate silica‐induced lung inflammation through an IL‐1β‐dependent mechanism

Abstract: Silicosis is an occupational lung disease caused by the inhalation of silica dust and characterized by lung inflammation and fibrosis. Interleukin (IL)-1β is induced by silica and functions as the key pro-inflammatory cytokine in this process. The Th17 response, which is induced by IL-1β, has been reported very important in chronic human lung inflammatory diseases. To elucidate the underlying mechanisms of IL-1β and IL-17 in silicosis, we used anakinra and an anti-IL-17 monoclonal antibody (mAb) to block the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 49 publications
2
39
0
Order By: Relevance
“…IL-1β production from effected cells has been found in many kinds of lung inflammatory reactions induced by viruses, bacteria and drugs1314. Some in vitro studies found that PM 2.5 could induce the secretion of IL-1β from macrophags through multiple pathways15.…”
mentioning
confidence: 99%
“…IL-1β production from effected cells has been found in many kinds of lung inflammatory reactions induced by viruses, bacteria and drugs1314. Some in vitro studies found that PM 2.5 could induce the secretion of IL-1β from macrophags through multiple pathways15.…”
mentioning
confidence: 99%
“…Altered expression levels of interleukins and tumor necrosis factora in response to inflammation have been observed in silicosis. [31][32][33] Baltimore et al 34 illustrated that the expression levels of interleukin-1 receptor-associated kinase 1 and tumor necrosis factor receptorassociated factor 6 were down regulated by administering a miR-146 oligonucleotide in target cells. Therefore, miR-146a may be involved in silicosis and pulmonary function through a variety of inflammatory cytokines, forming a complex regulatory network.…”
Section: Discussionmentioning
confidence: 98%
“…IL‐1β is a protein known by its crucial pathophysiological role in inflammatory disorders and its influence in silicosis susceptibility and/or severity has been investigated in several animal model studies, and in a clinical study . We hypothesized that there is a possible association of the IL1B +3954C>T polymorphism with the severity of silicosis, since this polymorphism has been previously associated with the severity and susceptibility to several inflammatory diseases .…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin 1 beta (IL‐1β), Interleukin 1 alpha (IL‐1α), and tumor necrosis factor‐alpha (TNF‐α) are proinflammatory cytokines associated with the physiopathology of both silicosis and Tb . They are encoded by polymorphic genes with a range of SNPs described, which can influence the activity or expression level of the codified proteins.…”
Section: Introductionmentioning
confidence: 99%